Revitalisasi dan Transformasi Penanganan Kawasan Kumuh di Kabupaten Tolitoli melalui Implementasi GIS dan Rekayasa Teknologi Informasi Hijau berbasis Ekologi - Pahude, Mansur S.; Purnomo, Dwi (Tolis Ilmiah : Jurnal Penelitian, 2025)
The problem of slum areas in Tolitoli Regency remains a strategic issue affecting the quality of life of the community. This condition is triggered by high population density, limited basic infrastructure, and inadequate sanitation systems. The central government, through Presidential Regulation No. 2 of 2015 in the 2015–2019 National Medium-Term Development Plan (RPJMN), has targeted the eradication of urban slum areas, in line with the Tolitoli Regency Government's commitment in the 2021–2026 RPJMD to reduce slum area by 30–60%. This requires innovative strategies oriented towards sustainability. This study was designed to formulate an ecology-based slum revitalization strategy with the support of GIS technology and green information systems. GIS spatial mapping was used to analyze existing conditions, identify risks, and map potential environmental improvements. The green technology approach is aimed at designing environmentally friendly and efficient solutions. Data were obtained through field surveys, satellite imagery interpretation, and interviews with government, community, and relevant institutions. The research's main outputs include a GIS-based digital slum map, an ecological revitalization strategy model, and policy recommendations for utilizing green technology. The findings are expected to strengthen the role of local governments in formulating data-driven policies and encourage multi-stakeholder collaboration to create healthy, livable, and sustainable residential areas in Tolitoli.